Morphometric analysis of the venom gland in worker bees of Apis mellifera (Hymenoptera : Apidae) from the pantanal region of Mato Grosso do Sul - Arruda, V. M.; Alves-Junior, V. V.; Chaud-Netto, J. [UNESP] (California State University, 2006)
In Apis mellifera the acid or venom gland is composed of secretory cells that surround a channel that opens into a reservoir devoid of musculature. This gland can at times present apical branching. In this study we recorded the frequency of branched venom glands in workers of Africanized bees (Apis mellifera Linnaeus) from six localities in the Pantanal region of Mato Grosso do Sul, and analyzed the relation among the length of the main duct, the length of the duct from the reservoir to the beginning of branching, the length of the branched segment (when present) and the total length of the gland. We sought to determine the probable genotypes of the bees from each population by using the model proposed by Alves-Junior. The frequency of branched glands varied from 50% to 83% in the worker bees coming from those places, indicating that this characteristic is primitive in these bees. The results of the Analysis of Discriminant Functions indicated significant differences in the morphometrical segments of the venom gland (Wilk's Lambda = 0.065; F-(27,F-30) = 4.507; P < 0.001), and permitted a differentiation of the populations studied. The genotypes inferred for the bees of each locality agree with the results obtained in the Analysis of Discriminant Functions and form three distinct groups, with some overlapping areas among them. In all of the populations considered the phenotype largevenom gland was predominant. It is inferred that bees with this phenotype (venom gland larger than S. 15 mm) have Gm(1) Gm(1) genotype, being therefore homozygotes for the major alleles and also for the modifier genes that codify this morphological trait. The high frequency of worker bees with large venom gland in all the places considered makes viable the development of a selection program in order to obtain bees with longer venom glands, aimed at the commercial production of venom by the beekeepers of the Pantanal region of Mato Grosso do Sul.
Keywords: Apis mellifera; Africanized honeybees; apitoxin; venom; acid gland; morphometry